UJI DAYA HAMBAT PERASAN JAHE MERAH (ZINGIBER OFFICINALE VAR RUBRUM) TERHADAP PERTUMBUHAN BAKTERI STAPHYLOCOCUS PIOGENIK DI LABORATORIUM TERPADU UNIVERSITAS ISLAM AL- AZHAR MATARAM 2019 - Helmi Yuliana; Rusmiatik (Nusantara Hasana Berdikari, 2022)
Pyogenic Staphylococcus bacteria is one of the bacteria that can infect the respiratory tract. Red ginger is a traditional plant containing flavonoids, phenols, essential oils, and tannins that function as antibacterial ingredients. This study aims to determine the inhibition of red ginger (Zingiber officinale var rubrum) juice against the growth of pyogenic Staphylococcus bacteria. The design carried out in this study was a completely randomized design (CRD) with 3 treatment groups consisting of red ginger (Zingiber officinale var rubrum) with a concentration of 20%, 40%, 60%, 80% and 2 control groups consisting of positive controls. (Ampicylin) and negative control using aquabides. After incubation, it was seen and measured the diameter of the inhibition zone called oligodynamic (empty area), using a ruler. All data obtained were statistically tested with One Way Anova which has a 95% confidence level (p value = 0.05) and with the help of SPSS to find out which concentrations were significant. The concentration of red ginger feeling shows the diameter of the inhibition zone on average that is 20% (12.67) mm, 40% (13.67) mm, 60% (14.67) mm, 80% (15.33) mm, all of them were effective against the growth of pyogenic Staphylococcus bacteria. Positive control using ampicylin showed a mean (22.00) mm. Based on the results of the One Way Anova statistical test, the p value is 0.000 or less than 0.05 so that there is an effect of red ginger juice on the growth of pyogenic Staphylococcus bacteria.